Inoculation of Merapi Indigenous Rhizobacteria as A Substitute Compost for Application in Rice Cultivation on Coastal Sandy Under Drought Stress - Sarjiyah Sarjiyah; Akhmad Bustamil; Agung Astuti (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
This study aimed to determine the role of the indigenous rhizobacteria from Merapi as a substitute for compost in rice cultivation on coastal sandy land under drought stress. The study was a single-factor experiment, with types and doses of compost as treatments, arranged in a completely randomized design (CRD) consisting of seven treatments and three replications. The seven treatments tested were cow manure compost at doses of 30 and 40 tons/ha, chicken manure compost at doses of 30 and 40 tons/ha, Azolla compost at doses of 20 and 30 tons/ha, and without compost as a control treatment. Each experimental unit consisted of three plants for destructive sampling, three sample plants, and a substitute plant. The application of cow manure compost at a dose of 30 tons/ha to the rice plants inoculated with MB and MD isolates of Merapi indigenous rhizobacteria resulted in the best growth at five weeks after planting, which was not significantly different from that without compost application. This result indicated that the rice plants cv. Segreng Handayani inoculated with Merapi indigenous rhizobacteria, cultivated on coastal sandy soil under drought stress, even without the application of compost, could give the same responses as the plants treated with various types and doses of compost.